Agenesis of second premolars in maxilla and mandible - A rare case report (Journal of Biomedical Sciences, 2015)
Congenital missing or absence of 6 or less teeth is known as Hypodontia which is a usual part of more complex set of developmental problems. Most cases of tooth agenesis involve hypodontia. In reference to second premolar, agenesis of a single second premolar is the most common form and occurrence of agenesis of four second premolars in both maxilla and mandible is not a very common condition.The purpose of this report is to describe a case of agenesis of a four second premolars in all the four quadrants in a 17 year old boy.Patient referred to the pediatric dentistry department as achief complaint of pain in the left lower back tooth region since one week. Clinical examination revealed the retained four primary second molars in both the arches of right and left sides and orthopantamograph confirmed the diagnosis. Pulpectomy was performed in maxillary left as well as mandibular left and right pimary molars and maxillary right second molar was grossly decayed which was extracted. In addition to case report, this article discusses possible etiological factors along with various treatment modalities.Journal of Biomedical Sciences 2015;2(2):12-16